Pemberdayaan Ibu-Ibu Melalui Pelatihan Pengolahan Bakso Ikan Louhan Di Pondok Pesantren Al-Manshurin - Kristina Haryati (UNIB Press, 2026)
Louhan fish, a predatory species within the Lake Sentani ecosystem, possesses significant potential for transformation into value-added commodities such as fishballs. This fishery product diversification not only enhances the economic value of local aquatic resources but also yields a food product characterized by an elastic, firm, and smooth texture. This community service initiative was designed to enhance the technical proficiency of local partners in diversifying Louhan fish processing. The program focused on a group of women at the Al-Manshurin Islamic Boarding School in Waena, Jayapura City, who previously lacked the creative expertise and technical knowledge required to utilize this species effectively. To address these challenges, the team implemented a comprehensive training program on fishball production. The methodology followed three systematic phases: educational socialization, hands-on production sessions, and a final evaluation. Twenty participants actively engaged in every stage, from theoretical instruction to physical processing. The results of this intervention demonstrated a remarkable outcome, with a 100% improvement in technical competency among all participants post-training. Consequently, the members of the Al-Manshurin Islamic Boarding School have acquired the independent skills necessary to produce Louhan fishballs, thereby fostering a local creative economy rooted in sustainable aquatic resource management.